AB1299 Functional capacity measured by haq in patients with rheumatic diseases in colombia. (12th June 2018) - Cuervo, F.M.; Santos, A.; Saldarriaga, E.L.; Rueda, J.C.; Angarita, I.; Ballesteros, J.; Peláez, I.; Forero, E.; Ramirez, J.; Londono, J.
Abstract : Background: Functional capacity is an important indicator of quality of life that is affected in different pathologies and is susceptible to intervention in early stages once it is recognised. In rheumatic diseases, functional limitation has a great impact that is evidenced by multiple degrees of long-term disability. Objectives: To evaluate the functional capacity in different rheumatic diseases by HAQ (Health Assessment Questionnaire) instrument. Methods: In the context of the prevalence study of rheumatic disease in Colombia, the assessment of functional capacity was measured by using the HAQ score, where functional limitation is scored in a range from 0 to 3 points according to the severity of limitation. The major functional limitation is scored 3 and not limitation 0. A total of 4020 individuals answered the questionnaire. Results: Patients with rheumatic diseases (n=2274) reported a greater degree of limitation compared with disease-free people (n=1104) or non-rheumatic patients (n=642) (p<0, 001). Especially patients with rheumatoid arthritis (RA) had the worst score (0.88±0, 72) compared to 0.06±0, 22 and 0.01±0, 14 of the population with non-rheumatic and healthy population, respectively (p<0.001). The HAQ score in the remaining diseases was 0, 67 (SD ±0, 62) for systemic lupus erythematosus (SLE), followed by patients with osteoarthrosis (OA) 0, 59 (SD ±0, 58), fibromyalgia (FM) 0, 56 (SD ±0, 57) and spondylarthritis (SpA) 0, 52 (SD ±0, 43). Functional capacity evaluated by HAQ, the points represent the mean of the instrument. * RA: Rheumatoid Arthritis; SLE: Systemic Lupus Erythematosus; OA: Osteoarthritis; FM: Fibromyalgia; SpA: Spondyloarthritis; CHIKV: Chikungunya fever; RRPS: Rheumatic Regional Pain Syndromes (Rotator cuff tendinopathy, shoulder bicipital tendinopathy, lateral and medial medial epicondylalgia, Quervain's tendinopathy, carpal tunnel syndrome, Dupuytren's contracture, trochanteric syndrome, anserine bursitis, achilles tendonopathy, plantar talalgia); NEMD: non-specific musculoskeletal disease. Conclusions: In comparison with disease-free population and non-rheumatic patients, the rheumatic patients had a lower functional capacity measured by HAQ. Patients with RA had more disability followed by patients with SLE and OA. Disclosure of Interest: None declared